2013
DOI: 10.5935/0101-2800.20130021
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for injury acute renal in patients with severe trauma and its effect on mortality

Abstract: The identification of these risk factors is of paramount importance for the development of care strategies for patients suffering from severe trauma, for the prevention of acute kidney injury and the associated high mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 17 publications
1
10
1
1
Order By: Relevance
“…[ 39 40 41 42 43 44 ] TBI triggers a series of catabolic processes that lead to reduced glomerular filtration and developing AKI that is further worsened by reduced renal perfusion pressure secondary to hypovolemia and shock. [ 42 45 ] Seventy-six percent deaths have been reported in these patients in TBI,[ 37 41 ] which is almost similar to our results (83.3% deaths). In our study, the risk of mortality increased by 24.7 times in TBI patients who developed AKI.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…[ 39 40 41 42 43 44 ] TBI triggers a series of catabolic processes that lead to reduced glomerular filtration and developing AKI that is further worsened by reduced renal perfusion pressure secondary to hypovolemia and shock. [ 42 45 ] Seventy-six percent deaths have been reported in these patients in TBI,[ 37 41 ] which is almost similar to our results (83.3% deaths). In our study, the risk of mortality increased by 24.7 times in TBI patients who developed AKI.…”
Section: Discussionsupporting
confidence: 90%
“…The incidence of AKI following trauma is reported from 0.098% to 17.3%. [ 7 36 37 38 39 40 ] The incidence of AKI in our study was 3.5%, while in Corral et al . 's study, it was 8%.…”
Section: Discussioncontrasting
confidence: 46%
“…After incorporation of currently available methods of classification, such as KDIGO, RIFLE and AKIN (all three based on creatinine changes and/or decrease of urine output), the overall incidence of 32.9% of AKI in our study is within the range of 16% to 39% found in the literature [ 10 , 11 ]. When looking separately at the incidence of AKI among trauma and non-trauma cases, the incidence of 36.6% among non-trauma patients is within the range shown above, although the AKI incidence of 28.6% among trauma patients is above the range of 6% to 17.3% found in the literature [ 6 , 12 , 13 ]. An explanation could be that trauma patients were more often severely ill, according to their higher APACHE II score compared to non-trauma cases.…”
Section: Discussionmentioning
confidence: 72%
“…Acute inpatient dialysis was found to be an inpatient variable predictive of tracheostomy and may serve as a marker of severity for non-neurological injuries. Although effects on tracheostomy have not been reported, acute kidney injury is a common complication in TBI patients with rates ranging from 9.2 to 23% [26][27][28][29]. Further work is needed to elucidate the relationship between the requirement for dialysis and tracheostomy, but fluid overload may play an important role.…”
Section: Discussionmentioning
confidence: 99%